Association between self-esteem and smoking among religous school students in Petaling District, Selangor - Olaitan, Jinadu Lukman; Md Said, Salmiah; Ariffin, Ahmad Azuhairi (The International Medical Journal of Malaysia, 2016)
Introduction: According to the Youth Behaviour Risk Factor Surveillance (YBRFSS, 2011) in Malaysia, the prevalence of smokers nationally among Form 1, 2 and 4 students government secondary school students was 9.1% (ever smokers) and 8.7% (current smokers). However, there is limited information on the prevalence of smoking among religious secondary school students and self-esteem as risk factor. Thus, this study was conducted to determine the prevalence and factors associated with smoking among the religious secondary school students in Petaling district, Selangor. Methods: A cross-sectional study was conducted among 899 students. The schools were selected using cluster sampling and self-administered questionnaire was used. Data was analyzed using chi-square test and multivariate logistic regression to identify the independent factors for smoking. Results: The response rate was 94%. The prevalence of ever smoking was 10.1%; 3.9% among female and 18.6% among male. The median age (interquartile range) of smoking initiation was 12.00 (4.01) years. The results showed that independent factors for smoking were: males (OR= 5.47); age group 14-15years (OR=2.82) and 16-17 years (OR=3.63) and having low self -esteem (OR=6.24). Conclusion: prevalence of ever smokers is higher when compared to YBRFSS, (2011) and it was revealed that most of the smokers started smoking even before secondary school. The results also revealed the importance of promoting self-esteem. Efforts in smoking prevention should therefore be focused on curbing the initiation of the acts and improving students’ self-worth.